Transcriptome and chemical analyses revealed the mechanism of flower color formation in Rosa rugosa - Wang, Yiting; Li, Shaopeng; Zhu, Ziqi; Xu, Zongda; Qi, Shuai; Xing, Shutang; Yu, Yunyan; Wu, Qikui (Frontiers in Plant Science, 2022)
Rosa rugosa is a famous Chinese traditional flower with high ornamental value and well environmental adapt ability. The cultivation of new colorful germplasms to improve monotonous flower color could promote its landscape application. However, the mechanism of flower color formation in R. rugosa remains unclear. In this study, combined analyses of the chemical and transcriptome were performed in the R. rugosa germplasms with representative flower colors. Among the identified anthocyanins, cyanidin 3,5-O-diglucoside (Cy3G5G) and peonidin 3,5-O-diglucoside (Pn3G5G) were the two dominant anthocyanins in the petals of R. rugosa. The sum content of Cy3G5G and Pn3G5G was responsible for the petal color intensity, such as pink or purple, light- or dark- red. The ratio of Cy3G5G to Pn3G5G was contributed to the petal color hue, that is, red or pink/purple. Maintaining both high relative and high absolute content of Cy3G5G may be the precondition for forming red-colored petals in R. rugosa. Cyanidin biosynthesis shunt was the dominant pathway for anthocyanin accumulation in R. rugosa, which may be the key reason for the presence of monotonous petal color in R. rugosa, mainly pink/purple. In the upstream pathway of cyanidin biosynthesis, 35 differentially expressed structural genes encoding 12 enzymes co-expressed to regulate the sum contents of Cy3G5G and Pn3G5G, and then determined the color intensity of petals. RrAOMT, involved in the downstream pathway of cyanidin biosynthesis, regulated the ratio of Cy3G5G to Pn3G5G via methylation and then determined the color hue of petals. It was worth mentioning that significantly higher delphinidin-3,5-O-diglucoside content and RrF3'5'H expression were detected from deep purple-red-flowered 8-16 germplasm with somewhat unique and visible blue hue. Three candidate key transcription factors identified by correlation analysis, RrMYB108, RrC1, and RrMYB114, might play critical roles in the control of petal color by regulating the expression of both RrAOMT and other multiple structural genes. These results provided novel insights into anthocyanin accumulation and flower coloration mechanism in R. rugosa, and the candidate key genes involved in anthocyanin biosynthesis could be valuable resources for the breeding of ornamental plants in future.